2019
DOI: 10.12688/f1000research.17649.2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of zoonotic tick-borne diseases in Latin America: Are we just seeing the tip of the iceberg?

Abstract: Ticks are responsible for transmission of multiple bacterial, parasitic and viral diseases. Tick-borne diseases (TBDs) occur particularly in tropical and also subtropical areas. The frequency of these TBDs has been increasing and extending to new territories in a significant way, partly since ticks’ populations are highly favored by prevailing factors such as change in land use patterns, and climate change. Therefore, in order to obtain accurate estimates of mortality, premature mortality, and disability assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Among the most vulnerable populations for these vector-borne diseases ( Bonilla-Aldana et al, 2021 ) are dogs ( Bonilla-Aldana et al, 2020b ; Rodriguez-Morales et al, 2018a ; Rodriguez-Morales et al, 2018b ). Multiple studies worldwide have assessed the prevalence of such diseases in canine populations ( Petruccelli et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the most vulnerable populations for these vector-borne diseases ( Bonilla-Aldana et al, 2021 ) are dogs ( Bonilla-Aldana et al, 2020b ; Rodriguez-Morales et al, 2018a ; Rodriguez-Morales et al, 2018b ). Multiple studies worldwide have assessed the prevalence of such diseases in canine populations ( Petruccelli et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…South America, for example, is represented in the tick mapping literature by only two studies conducted in Brazil, despite having confirmed cases of tick-borne diseases and known tick species of medical importance ( Guglielmone et al 2006 ). Documentation of zoonotic pathogens on the continent is similarly underfunded, and tick-borne transmission cycles are an active area of research ( Guglielmone et al 2006 , Rodriguez-Morales et al 2018 ). Identifying regional priorities for surveillance based on clinical and veterinary significance, and expanding the purview of tick-borne disease mapping using participatory approaches alongside quantitative and GIS work, will help manage the burden of tick-borne disease where it remains the highest.…”
Section: Discussionmentioning
confidence: 99%
“…In Colombia and the surrounding tropical and subtropical regions, there is a significant prevalence of vector-borne haemoparasitic infections [113] that induce anaemia, fever, wasting, and reproductive dysfunction [114]. These diseases are primarily caused by eukaryotic parasites within the Babesia [115] and Trypanosoma [116] genera, and bacterial pathogens from the Anaplasma genus [117].…”
Section: Discussionmentioning
confidence: 99%